(untitled) (Global Journal of Management and Business Research, 2014)
The utilization of operating theatres and efficiency of nurse scheduling has an impact on patient outcomes, hospital finances and clinical effectiveness. To date, research has tended to focus on the output rather than on the process of nurse scheduling. We report on use of the Lean mapping tool, Makigami, in operating room (OR) nurse scheduling. This study was conducted at a large surgical department in the Netherlands. A multidisciplinary team of nine health-care professionals used Makigami, includingfive steps: (1) mapping the current state of OR nurse scheduling, (2) setting the ideal state and the first target condition, (3) performing a fishbone analysis, (4) conducting actions and (5) mapping the revised process of OR nurse scheduling. The current OR nurse scheduling process showed 44 transfers, 42 documents and 64 types of waste, which collectively led to 35 errors in 7 days. The first target condition was to guarantee quality of care:the right employees, at the right time, in the right place without errors. The revised process, as a result of the action plans that emerged through the fishbone analysis, led to an outcome of two errors in 7 days with a reduction in waste of 41%. The use of Makigami led to an optimized OR nurse scheduling process: the right OR nurses, with the right qualifications, were scheduled for the right surgical procedures. A focus on process led to a reduction in transfers and errors, which indicate a higher quality of care.